Model Public Speaking Kyai dalam Menanamkan Nilai-Nilai Pendidikan pada Jamaah Majelis Doa dan Taklim At-Taqwa Wonokromo Pleret Bantul DIY - Munip, Abdul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
Islamic educational activities can take place anywhere, including in the Majelis Doa and Taklim At-Taqwa at Wonokromo, Pleret, Bantul. In general, the informal education activitieslike have not sustained for long times, however mujahadah weekly activities of the Majelis has been going on for 22years with the number of jamaah or adherents over 3000 people, there is even a tendency of increasing the number of jamaah. By a qualitative approach through participant observation and in-depth interviews, the article writer finds three things that underlie this fact. First, KH. Abdul Khaliq Syifa as a leader of Majelis applied a model of public speaking that combine all the elements of the speaker, the listener, message, medium, feedback, interference, and situation. Judging from the purpose of public speaking, Kyai Khaliqâs lecturesare more patterned informative, persuasive, argumentative, educational, and entertainment. That is why, he talks very positive impact on the audiences or jamaah. Secondly, there are two values of Islamic education imparted to the jamaah, i.e practical and theoretical values. The practical value is shown in the form of exercise and refraction for zikr through the reading of al-Fatihah 41 times then followed by tahlil. While the theoretical values are Islamic teachings writen in the Mukhtarul Ahadith which includes the dimensions of aqidah, fiqh, morality, mysticism, and others. Third, based on the narrative of the jamaah, the mujahadah activities in the Majelis Doa dan Taklim At-Taqwa have positive impactson increasing spirituality and the meaning of their lives. Among the positive impacts occur on the satisfaction of their spirituality, their religious quality and their socio-economic benefitsÂ ÙÙÙÙÙ ÙÙØ£ÙØ´Ø·Ø© Ø§ÙØªØ¹ÙÙÙÙØ© Ø£Ù ØªØªØ®Ø° ÙÙ Ø£Ù ÙÙØ§Ù ÙÙØ§ Ø³ÙÙØ§ ÙÙÙØ¬ÙØ³"Ø§ÙØªÙÙÙ" ÙÙ Ø§ÙØ¯Ø¹Ø§Ø¡ Ù Ø§ÙØªØ¹ÙÙÙØ§ÙØ°Ù ÙÙØ¹ ÙÙ ÙÙÙÙÙØ±ÙÙÙØ ÙÙÙØ±ÙØªØ Ø¨Ø§ÙØªÙÙ.Ø¨ÙÙÙØ§ ÙØ«ÙØ± ÙÙ Ø§ÙØ£ÙØ´Ø·Ø© Ø§ÙØªØ¹ÙÙÙÙØ© ØºÙØ± Ø§ÙÙØ¸Ø§ÙÙØ© ÙÙ ÙØ¯Ù Ø·ÙÙÙØ§Ø ÙÙÙÙ Ø§ÙÙØ¬Ø§ÙØ¯Ø©Ø§ÙØ£Ø³Ø¨ÙØ¹ÙØ©ÙÙ ÙØ°Ø§Ø§ÙÙØ¬ÙØ³ ÙØ¯ Ø¨ÙÙØªØ§ÙÙ 22Ø³ÙØ© ÙÙØ´Ø§Ø±Ù ÙÙÙØ§ Ø£ÙØ«Ø± ÙÙ 3000 Ø´Ø®ØµØ Ø¨Ù ÙØ²Ø¯Ø§Ø¯ ÙÙ ÙÙ ÙÙØª. ÙØ¨ØªØ·Ø¨ÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙÙÙØ¹Ù ÙÙ Ø§ÙØ¨ØØ« ÙØ¬Ø¯ Ø§ÙÙØ§ØªØ¨ ÙÙ Ø®ÙØ§Ù Ø§ÙÙÙØ§ØØ¸Ø© Ø¨Ø§ÙÙØ´Ø§Ø±ÙØ© ÙØ§ÙÙÙØ§Ø¨ÙØ§Øª Ø§ÙÙØªØ¹ÙÙØ©ØØ§Ù ÙÙØ§Ù Ø«ÙØ§Ø«Ø© Ø£Ø´ÙØ§Ø¡ Ø§ÙØªÙ ØªÙÙÙ ÙØ±Ø§Ø¡ ÙØ°Ù Ø§ÙØÙÙÙØ©. Ø£ÙÙØ§ØØ§Ù Ø§ÙØ´ÙØ® Ø¹Ø¨Ø¯ Ø§ÙØ®Ø§ÙÙ Ø´ÙØ§Ø¡ ÙÙØ¹ÙÙ ÙÙ ÙØ°Ø§ Ø§ÙÙØ¬ÙØ³ÙØ§Ø¯Ø±Ø¹ÙÙ Ø§ÙØ¬ÙØ¹ Ø¨ÙÙ Ø¬ÙÙØ¹ Ø¹ÙØ§ØµØ±Ø§ÙØ®Ø·Ø§Ø¨Ø© Ø§ÙØ¹Ø§ÙÙØ© ÙÙ Ø§ÙÙØªÙÙÙØ ÙØ§ÙÙØ³ØªÙØ¹ÙÙØ ÙØ±Ø³Ø§ÙØ©Ø ÙØ§ÙÙØªÙØ³Ø·Ø©Ø ÙØ±Ø¯ÙØ¯ Ø§ÙÙØ¹ÙØ ÙØ§ÙØªØ¯Ø®ÙØ ÙØ§ÙÙØ¶Ø¹. Ø§ÙØ·ÙØ§ÙØ§ ÙÙ Ø§ØºØ±Ø§Ø¶ Ø§ÙØ®Ø·Ø§Ø¨Ø© Ø§ÙØ¹Ø§ÙÙØ©Ø ØªÙÙÙ ÙØØ§Ø¶Ø±Ø§Øª Ø§ÙØ´ÙØ® Ø¹Ø¨Ø¯ Ø§ÙØ®Ø§ÙÙ Ø£ÙØ«Ø± ÙÙØ· Ø¨Ø§ÙÙØ¹ÙÙÙØ§ØªØ ÙÙÙÙØ¹Ø©Ø ÙØ¬Ø¯ÙÙØ©Ø ÙØ§ÙØªØ¹ÙÙÙÙØ©Ø ÙØ§ÙØªØ±ÙÙÙÙØ©. ÙØ°Ø§ ÙÙ Ø§ÙØ³Ø¨Ø¨Ø ÙÙ Ø§ÙÙØØ§Ø¶Ø±Ø§ØªÙ ÙØ¯ ØªØ£Ø«Ø±Øª Ø¥ÙØ¬Ø§Ø¨ÙØ© Ø¬Ø¯Ø§ Ø¹ÙÙ ÙÙÙØ³ Ø§ÙØØ§ Ø¶Ø±ÙÙÙØ§ÙÙØ³ØªÙØ¹ÙÙ. Ø«Ø§ÙÙØ§Ø Ø§Ù ÙÙØ§Ù ÙÙØ¹ÙÙ ÙÙ ÙÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙÙÙÙÙÙØ© Ø¥ÙÙ Ø§ÙØØ§ Ø¶Ø±ÙÙØ ÙÙÙØ§ Ø§ÙÙÙÙØ© Ø§ÙØ¹ÙÙÙØ© ÙØ§ÙÙØ¸Ø±ÙØ©. ÙØªØªØÙÙØ§ÙÙÙÙØ© Ø§ÙØ¹ÙÙÙØ© ÙÙ ÙÙØ§Ø±Ø³Ø© Ø§ÙØ°ÙØ± Ø¬ÙØ§Ø¹Ø©Ø¨ÙØ±Ø§Ø¡Ø© Ø³ÙØ±Ø© Ø§ÙÙØ§ØªØØ© 41 ÙØ±Ø© Ø«Ù ÙÙÙÙØ§ Ø§ÙØªÙÙÙÙ. ÙØ£ÙØ§ Ø§ÙÙÙÙØ© Ø§ÙÙØ¸Ø±ÙØ© ÙØªØªØÙÙ ÙÙ Ø®ÙØ§Ù ÙØØ§Ø¶Ø±Ø§Øª Ø§ÙØ´ÙØ® Ø¹Ø¨Ø¯ Ø§ÙØ®Ø§ÙÙ Ø§ÙÙÙÙÙÙØ© ÙÙ ÙØªØ§Ø¨ ÙØ®ØªØ§Ø±Ø§ÙØ£ØØ§Ø¯ÙØ« ÙØªØ¨ÙØ§ Ø§ÙØ´ÙØ® Ø§ÙÙØ§Ø´ÙÙ. ÙÙØ´ØªÙÙ ÙØ°Ø§ Ø§ÙÙØªØ§Ø¨ Ø§ÙØ¹ÙÙØ¯Ø© ÙØ§ÙÙÙÙ ÙØ§ÙØ£Ø®ÙØ§Ù ÙØ§ÙØªØµÙÙ ÙØºÙØ±ÙØ§. Ø«Ø§ÙØ«Ø§Ø Ø§Ø³ØªÙØ§Ø¯Ø§ Ø¥ÙÙ Ø§ÙØ±ÙØ§ÙØ© ÙÙ Ø§Ø§ÙØØ§Ø¶Ø±ÙÙ ÙØ§ÙÙØ´Ø§Ø±ÙÙÙØØ£Ù Ø§ÙÙØ¬Ø§ÙØ¯Ø©Ø§ÙØ£Ø³Ø¨ÙØ¹ÙØ© ÙÙ ÙØ°Ø§Ø§ÙÙØ¬ÙØ³ÙØ¯ ØªØ£Ø«Ø±Øª Ø¥ÙØ¬Ø§Ø¨ÙØ© Ø¬Ø¯Ø§ Ø¹ÙÙ Ø²ÙØ§Ø¯Ø© Ø§ÙØ¥ÙÙØ§Ù ÙÙ ÙÙÙØ³ÙÙ ÙÙØ¹ÙÙ ØÙØ§ØªÙÙ. ÙÙÙ Ø§ÙØ¢Ø«Ø§Ø± Ø§ÙØ¥ÙØ¬Ø§Ø¨ÙØ©ÙØ¯ÙÙÙ Ø§ÙÙÙ ÙØ¯ Ø±Ø¶ÙØ§ ÙÙÙØ¹ÙØ§ Ø§ÙÙ Ø´Ø¹ÙØ± Ø¯ÙÙÙÙØ§ÙØ±ÙØÙØ©Ø ÙØµÙØ§Ø Ø§Ø¹ÙØ§ÙÙÙ Ø§ÙØ¯ÙÙÙØ©Ø ÙØ§ÙÙÙØ§ÙØ¹ Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ© ÙØ§ÙØ§ÙØªØµØ§Ø¯ÙØ© ÙØ¯ÙÙÙ